Analysis of prototype options for closing the digital divide in the concession area of Coopesca R.L. (National Administration Journal, 2025)
This research analyzes options for closing the digital divide through the use of prototypes to establish viable solutions according to the environment of dispersed and remote rural communities, applying Cost-Benefit Analysis (CBA). With the support of Coopelesca R.L., the district of Cutris de San Carlos was studied. The CBA showed that, financially, the proposed solutions are not viable; closing the digital divide is achieved through the solidarity contribution of the members. Without contributions from FONATEL, Social Economy, or public policy resources, the digital divide will not decrease. Prototype analysis is an option that should continue to be applied to seek creative, needs-oriented, and solidarity-based solutions.
Keywords: Digital divide; social economy; solidarity; prototypes; viability; dispersed communities